A flexible approach to the mapping of intonational phrases*. Issue 1 (3rd August 2015) - Hamlaoui, Fatima; Szendrői, Kriszta
<x content-type="archive" xml:space="preserve">Abstract</x> We propose that for the syntax–prosody mapping of clauses and intonational phrases, the notion of 'clause' should be determined in a flexible manner, making reference to the highest position to which the verbal material (i.e. the verb itself, the inflection, an auxiliary or a question particle) is overtly moved or inserted, together with the material in its specifier. This contrasts with rigid approaches, which assume that mapping is based on particular functional heads. We provide support for this proposal with data from the Bantu language Bàsàá and the Finno-Ugric language Hungarian, showing that a left-peripheral constituent may be prosodically outside the core intonational phrase even though its syntactic position is relatively low, as long as the verb is even lower, and, conversely, that a constituent may be phrased inside the core intonational phrase even if it is in a syntactically high position, as long as the verb is also high.